Post-angiography Retention of the Contrast Agent in the Left Atrial Appendage Is Associated With Risk of Cardioembolic Stroke in Patients With Atrial Fibrillation: A Retrospective Study - Fang, Ping; Wei, Youquan; Wang, Jinfeng; Wang, Xianghai; Yang, Hao (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) represents an important risk factor for cardioembolic stroke, and most atrial thrombi originate from the left atrial appendage (LAA). Although the CHA2DS2-VASc score is widely used to estimate the risk of cardioembolic stroke in AF patients, yet greatly affected by many factors. This study was undertaken to determine the association between contrast agent retention in LAA after LAA angiography and risks of cardioembolic stroke in patients with AF. Methods: This is a retrospective study. The demographic and clinical data of AF patients undergone left atrial appendage occlusion (LAAO) with or without catheter radiofrequency ablation were retrospectively analyzed. The patients were classified into either stroke or non-stroke group by the history with cardioembolic stroke or transient ischemic attack (TIA). Results: Sixty-two consecutive patients undergone LAAO were finally included, in whom 31 AF patients had a history of cardioembolic stroke or TIA (one TIA), and significantly higher CHA2DS2-VASc score (4.2 ± 1.4 vs. 3.3 ± 1.3; P = 0.006) as well as incidence of contrast agent retention in LAA (n = 20 vs. n = 7; P = 0.001) compared to the patients in non-stroke group. In addition, the relative proportion of distinctive morphological types of LAA was significantly different between groups (P < 0.001). Multivariate logistic regression analysis showed that higher CHA2DS2-VASc scores (OR = 1.7, 95% CI: 1.0–3.0, P = 0.046) and LAA contrast agent retention (OR = 5.1, 95% CI: 1.1–23.9, P = 0.002) were associated with increased risks of cardioembolic stroke. The patients with Windsock type LAA (OR = 7.8, 95% CI: 1.1–57.2, P = 0.044) and Cauliflower LAA (OR = 20.2, 95% CI: 3.2–125.5, P = 0.001) were more prone to cardioembolic stroke compared to those with Chicken Wing type LAA. Conclusion: Left atrial appendage contrast agent retention after LAA angiography is associated with the risks of cardioembolic stroke in patients with AF, and cardioembolic stroke is more seen in AF patients with Windsock or Cauliflower type LAA.